PERANAN GEREJA TERHADAP JEMAAT TERDAMPAK COVID-19 DALAM MASA PANDEMI MENURUT MATIUS 5:13-16 - Tabita Kustiati (Jurnal Teologi Biblika, 2022)
The emergence of Covid-19 has greatly impacted the Indonesian people who opened God's congregations during the outbreak of covid-19, many church members, one of which was because the congregation who was declared positive, died, there were congregations who were laid off from work, economic difficulties and so on. Therefore, the role of the church is important in this pandemic period to continue to provide support so that the faithful congregation can continue to live as God's people. This research is to examine in depth and objectivity of the influence in the pandemic period for the church set by Matthew 5:13-16. This study uses a qualitative research method of taxonomic analysis, using inductive biblical research based on analysis with three sub-focuses: 1) the church is salt, 2) the church is light, 3) the church is an example in good deeds. The results of the study indicate that the church must have a positive influence on its congregation, providing a real dedication to the community congregation and the congregation in particular.